2016
DOI: 10.4028/www.scientific.net/msf.877.655
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Wavy Interface Formation and Successive Temperature Change in Magnetic Pulse Welded Al/Cu Joint

Abstract: Magnetic pulse welding (MPW) which is one of the impact welding methods is suitable for a wide variety of combinations of similar and dissimilar metals. The flyer plate is accelerated by electromagnetic force and collided to the parent plate. A characteristic wavy interface is formed. The impact velocity and impact angle of the flyer plate during impact are important parameters which affect the interface morphology. In the case of dissimilar metals (e.g. Al/Cu, Al/Fe), the intermediate layer (such as intermeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the temperature rise has been investigated by numerical analysis. Nishiwaki et al performed a numerical analysis of the temperature rise at the Al/Cu wavy interface during magnetic pulse welding, and reported that the temperature of the vortex part of the wavy interface reached approximately 3000 K. 28) This temperature is much higher than the melting point of Al (933 K). The melting point of metal under high pressure is known to differ from that under atmospheric pressure, and it is reported that the melting point of Al increases almost linearly from 933 K to 1050 K when the pressure is increased from atmospheric pressure to 2 GPa.…”
Section: Morphology Of Welding Interfacementioning
confidence: 99%
“…Therefore, the temperature rise has been investigated by numerical analysis. Nishiwaki et al performed a numerical analysis of the temperature rise at the Al/Cu wavy interface during magnetic pulse welding, and reported that the temperature of the vortex part of the wavy interface reached approximately 3000 K. 28) This temperature is much higher than the melting point of Al (933 K). The melting point of metal under high pressure is known to differ from that under atmospheric pressure, and it is reported that the melting point of Al increases almost linearly from 933 K to 1050 K when the pressure is increased from atmospheric pressure to 2 GPa.…”
Section: Morphology Of Welding Interfacementioning
confidence: 99%
“…Numerical simulation is a good tool to understand the temperature during the welding process. Nishiwaki investigated temperature at the wavy aluminum/copper welding interface during magnetic pulse welding using smoothed particle hy- drodynamics 28) . They reported that the temperature of vortex zone produced at the wavy interface exceeds the melting points of copper (2899 K).…”
Section: Microstructure Of Cu/ni Welding Interfacementioning
confidence: 99%